2007
DOI: 10.5194/nhess-7-523-2007
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture storage and hillslope stability

Abstract: Abstract.Recently, we presented a steady-state analytical hillslope stability model to study rain-induced shallow landslides. This model is based on kinematic wave dynamics of saturated subsurface storage and the infinite slope stability assumption. Here we apply the model to investigate the effect of neglecting the unsaturated storage on the assessment of slope stability in the steady-state hydrology. For that purpose we extend the hydrological model to compute the soil pore pressure distribution over the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…Las curvas de la FIGURA 4 se obtuvieron a partir de la ecuación 8, al considerar γ m = 1000 Kgm -3 , γ s = 1600 Kgm -3 y γ b = 600 Kgm -3 , siendo respectivamente el peso específico del agua, saturación y boyante (Talebi et al, 2007). Para este escenario se encuentra estable la ladera a lo largo del perfil para los periodos continuos de precipitación.…”
Section: Resultados De La Predicción De La Saturación De La Zona Teóricaunclassified
See 1 more Smart Citation
“…Las curvas de la FIGURA 4 se obtuvieron a partir de la ecuación 8, al considerar γ m = 1000 Kgm -3 , γ s = 1600 Kgm -3 y γ b = 600 Kgm -3 , siendo respectivamente el peso específico del agua, saturación y boyante (Talebi et al, 2007). Para este escenario se encuentra estable la ladera a lo largo del perfil para los periodos continuos de precipitación.…”
Section: Resultados De La Predicción De La Saturación De La Zona Teóricaunclassified
“…Un método para calcular el factor de seguridad en una pendiente infinita con una zona no saturada fue propuesta por Talebi et al (2007Talebi et al ( , 2008. Se asume que el nivel freático, el peso unitario de húmedo y la cohesión del suelo dependen de la coordenada x.…”
Section: Geometría De La Laderaunclassified
“…A number of studies, similar to this study, have linked slope hydrology to instability mechanism in the topographic hollows (Sidle 1987;Montgomery & Dietrich 1994;D'odorico & Fagherazzi 2003;Talebi et al 2007). Some monitoring studies have discussed the response of soil in a topographic hollow such as variation in subsurface run-off, porewater pressure, and temperature during a heavy rainstorm (Fannin & Jaakkola 1999;Uchida et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…This is called the event-limited regime. Hence, it can be concluded that hollow geometry is an important control on subsurface flow response Hilbert et al, 2004) and this process affects slope stability (Talebi et al, 2007). Figure 2 shows long term simulations of deposit thickness evolution in the four hollows (from top to bottom) and illustrates how shallow landsliding occurs when the soil thickness (D) ranges between D cr and D max .…”
Section: Resultsmentioning
confidence: 99%
“…From the topography view point, in most models of slope stability only the slope angle is considered. Although slope gradient is an important factor in landslide initiation, other geometric characteristics (such as profile curvature and plan shape) also control the hydrological process (Hilberts et al, 2004) and as such affect hillslope stability (Talebi et al, 2007). The plan shape defines topographic convergence, which is an important control on subsurface flow concentration.…”
Section: Hollow Geometrymentioning
confidence: 99%